Challenging the Patriarchal Barriers: The Role of Women Activists and Their Advocacy for Domestic Violence in Semarang City, Central Java - Zahwa, Alya Meuthia (UI Scholars Hub, 2021)
Domestic violence is the most common form of violence experienced by women in Indonesia. It has become a social issue for women activists to seek a solution. However, many women activists have to face challenges, both structural challenges, and cultural challenges, as experienced by women activists at the Legal Resources Center-Gender Justice and Human Rights (LRC-KJHAM) in Semarang City. This article argues that challenges at the structural and cultural levels ultimately become obstacles for women activists from the LRC-KJHAM in fighting for rights and justice for women victims of violence, as well as creating a climate of gender equality in Semarang City. This argument is based on the results of qualitative research on LRC-KJHAM activists in Semarang City within the framework of Margaret Archer’s theoretical analysis of morphogenesis.